2023
DOI: 10.1101/2023.11.30.569496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prostate cancer-induced endothelial-to-osteoblast transition generates an immunosuppressive bone tumor microenvironment

Guoyu Yu,
Paul G. Corn,
Celia Sze Ling Mak
et al.

Abstract: Immune checkpoint therapy has limited efficacy for patients with bone metastatic castrate-resistant prostate cancer (bmCRPC). In this study, we revealed a novel mechanism that may account for the relative resistance of bmCRPC to immune checkpoint therapy. We found that prostate cancer (PCa)-induced bone via endothelial-to-osteoblast (EC-to-OSB) transition causes an ingress of M2-like macrophages, leading to an immunosuppressive bone tumor microenvironment (bone-TME). Analysis of a bmCRPC RNA-seq dataset reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“… 70 Numbers of CD206+ M2 macrophages are increased in castrate resistant disease 70 , 87 , 88 , 89 and consistent with our findings for ST6GAL1, a recent study showed CD206+ M2 macrophages are upregulated in bone metastatic CRPC specimens compared with primary tumours or lymph node metastases. 90 M2 like macrophages can secrete pro-metastatic factors and cytokines to suppress immune responses initiated by T cell leading to immunological silence 91 and strategies to target prostate tumour TAMs are being investigated as approaches to re-sensitise the prostate TME to immunotherapy. 66 , 92 Previous studies have implicated tumour-derived sialic acids with the differentiation of monocytes to macrophages with a pathogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 70 Numbers of CD206+ M2 macrophages are increased in castrate resistant disease 70 , 87 , 88 , 89 and consistent with our findings for ST6GAL1, a recent study showed CD206+ M2 macrophages are upregulated in bone metastatic CRPC specimens compared with primary tumours or lymph node metastases. 90 M2 like macrophages can secrete pro-metastatic factors and cytokines to suppress immune responses initiated by T cell leading to immunological silence 91 and strategies to target prostate tumour TAMs are being investigated as approaches to re-sensitise the prostate TME to immunotherapy. 66 , 92 Previous studies have implicated tumour-derived sialic acids with the differentiation of monocytes to macrophages with a pathogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%